EQA total haemoglobine quantification: long-term analytical performance for thirty Portuguese Laboratories - Miranda, Armandina (2016)
Total haemoglobin is one of the most frequently ordered laboratory tests, both in the hospital and ambulatory. Haemoglobin concentration provides information about the status of anaemia in the population and guides many clinical diagnoses and therapeutic interventions. Portuguese External Quality Evaluation Program (PNAEQ) provides 4 survey per year with 2 samples each since it is important for medical laboratories to know about the stability and performance of their methods over the time. The main objective of this study was to apply a linear regression model for long-term evaluation of the performance of laboratories in haemoglobin quantification by comparing the laboratory individual results with the consensus mean of each round, after outliers exclusion. To evaluate the performance of the laboratory, the long-term analytical CV (LCVa) and the total analytical bias were established.